Diseminasi Prinsip 3R (Reduce, Reuse, Dan Recycle) melalui Pengolahan Sampah menjadi Media Tanam Hidroponik - Umardiyah, Fitri; Lukmana, Lutfi Fahmi; Rohmah, Imama Tur; Satiti, Wisnu Siwi; Nur, Luluk Choirun Nisak (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
One of the programs to handle waste problems is through the 3R program, namely reduce or reduce the amount of waste, recyle or recycle waste, and reuse or reuse waste. Processing waste into hydroponic planting media can reduce the amount of waste while utilizing it to grow organic vegetables with economic value. This activity was attended by 15 youths of Kudubanjar Village youth organization. The activity was divided into two stages, namely socialization and practice. The socialization stage was carried out using lecture and discussion methods. Next is the practice of making hydroponic planting media. This activity provides additional insight and knowledge as well as skills to the community, especially youth groups related to processing used bottle waste as hydroponic planting media. This activity also provides community knowledge about one of the ways to process used bottle waste that is useful.